Balancing Managerialism and Autonomy: A Panel Study of the Link Between Managerial Autonomy, Performance Goals, and Organizational Performance. Issue 6 (2nd November 2022) - Bjørnholt, Bente; Boye, Stefan; Mikkelsen, Maria Falk
Abstract: This article provides new evidence on the relationship between managerial autonomy, use of performance goals, and public service performance. Previous empirical studies have found seemingly inconsistent effects of managerial autonomy. As interests of agents may differ from wishes of principals, effects of autonomy may depend on whether superjacent levels couple managerial autonomy with a high focus on performance goals. Linking three waves of panel survey data from Danish school principals, local government, and student-level data, this article is able to rigorously test the link between managerial autonomy, use of performance goals, and organizational performance, measured as student achievements and student self-efficacy. We find that when managerial autonomy is accompanied by high use of performance goals from superjacent levels, there is evidence of performance improvement. Furthermore, when managerial autonomy and performance goals do not go hand in hand, organizational performance may even suffer.